2008
DOI: 10.1107/s0108767308089605
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human DAAM1 formin homology 2 domain

Abstract: Posttranslational modification by ubiquitin regulates a broad range of cellular activities such as protein degradation, transcriptional regulation, endocytosis, and DNA repair. p62 is one of the proteins which is known to recognize poly-linked ubiquitin chains through the ubiquitin associated (UBA) domain. Physiological function of p62 is implicated in the formation of protein inclusions which can be observed in neurodegenerative diseases such as Huntington's disease. p62 is known to accumulate in ubiquitin-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…C-terminal Fmn-2 sequences (accession number Q9NZ56) encompassing the FH2 domain and FSI sequence motif have been modeled with the HHpred server. The resulting structural model of the Fmn-2 C-terminus superimposed perfectly with the crystal structure of the Daam1 FH2 dimer (PDB ID: 2Z6E) (Yamashita et al, 2007) and the Fmn-2-FSI crystal structure (PDB ID: 2YLE, 3R7G) (Vizcarra et al, 2011;Zeth et al, 2011) at the very C-terminal end. This enabled us to include the Spir-1-KIND structural data from the KIND/FSI complex (PDB ID: 2YLE) into our model structure.…”
Section: Actin Nucleation By the Spir/fmn Complexmentioning
confidence: 66%
“…C-terminal Fmn-2 sequences (accession number Q9NZ56) encompassing the FH2 domain and FSI sequence motif have been modeled with the HHpred server. The resulting structural model of the Fmn-2 C-terminus superimposed perfectly with the crystal structure of the Daam1 FH2 dimer (PDB ID: 2Z6E) (Yamashita et al, 2007) and the Fmn-2-FSI crystal structure (PDB ID: 2YLE, 3R7G) (Vizcarra et al, 2011;Zeth et al, 2011) at the very C-terminal end. This enabled us to include the Spir-1-KIND structural data from the KIND/FSI complex (PDB ID: 2YLE) into our model structure.…”
Section: Actin Nucleation By the Spir/fmn Complexmentioning
confidence: 66%
“…1C). Recent structural studies have shown that the conformation of the Daam1 FH2 domain is stabilized by the -sheet-like structure within this coil-coiled region, suggesting a regulatory role for this linker region (Lu et al, 2007;Yamashita et al, 2007). Molecules that bind this FH2 linker region might regulate the ability of the FH2 domain of Daam1 to mediate actin nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…This isoleucine is present in all formins examined in yeast and metazoans ( Ref. 1 and further unpublished sequence analysis), and the side chain protrudes toward the center of the FH2 donut from an ␣ helix in the knob, according to crystal structures of Bni1p, DAAM1, mDia1, and FMNL3 (14,30,39,44). 3 In the Bni1p/actin co-crystal (44), the isoleucine side chain engages in interactions with residues at the "barbed end cleft" of actin between subdomains 1 and 3, a similar position to that occupied by WH2 domains (45).…”
Section: Discussionmentioning
confidence: 99%